"THE ECONOMIC AND POLITICAL SIGNIFICANCE OF IDEOLOGICAL EDUCATION AND IDEOLOGICAL FACTORS IN THE DEVELOPMENT OF THE YOUTH IDIASPHERE" - Nurbek Ahmatov Shukurullo o'g'li (Journals Park Publishing, 2023)
This article talks about the economic and political importance of ideological education and ideological factors in the development of the youth sphere. The author clarified the problem on the basis of available scientific literature, relying on literary data and written sources. Comparative analysis of existing specific approaches and theories on the economic and political importance of ideological education and ideological factors in the development of the youth sphere.
Keywords: Youth, idiosphere, development, idea, education, ideology, factors.